Safety and efficacy of pirfenidone and nintedanib in patients with idiopathic pulmonary fibrosis and carrying a telomere-related gene mutation. Issue 2 (11th February 2021) - Justet, Aurélien; Klay, Dymph; Porcher, Raphaël; Cottin, Vincent; Ahmad, Kais; Molina Molina, Maria; Nunes, Hilario; Reynaud-Gaubert, Martine; Naccache, Jean Marc; Manali, Effrosyni; Froidure, Antoine; Jouneau, Stéphane; et al.
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive and deadly interstitial lung disease (ILD). Over the past decade, familial occurrence of IPF led to the identification of genetic susceptibility traits [1]. Germline pathogenic variations in telomere-related genes (TRG) such as TERT, TERC TINF2, DKC1, RTEL1, PARN, NAF1, ZCCHC8, NHP2 and NOP10 have been detected in 20–30% of patients with familial pulmonary fibrosis (FPF) and in 1–5% of sporadic IPF [2–4]. In comparison with IPF patients, carriers of a TRG mutation are significantly younger and show an accelerated decline of forced vital capacity (FVC) [5–7]. Two drugs, pirfenidone and nintedanib, have been shown to reduce the decline of FVC in IPF patients [8, 9]. So far, two studies have reported on the safety and effectiveness of pirfenidone in patients with a TRG mutation [6, 7] whereas no study has investigated nintedanib in this specific population. Thus, the aim of this retrospective study was to assess safety and efficacy of nintedanib and pirfenidone in IPF patients with a TRG mutation. This study suggests that pirfenidone and nintedanib can be used safely in IPF patients with a telomerase related gene mutation and that both drugs reduce FVC decline. These results should be confirmed in a larger prospective study. https://bit.ly/3k7b4Zx